(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Schwenkia americana Linn plant has been used in traditional medicine for the treatment of different pathologies such as cough, headache, fever, sinusitis, including gastric ulcer. This study investigated the healing effect of crude flavonoid on aspirin-induced gastric ulcer in rats. Thirty-six rats were used for the study. Ulcer was induced in experimental animals in group II to VI with 500mg/kg body weight of aspirin for three days. Group I which served as negative control received normal saline and was not induced. The ulcerated animals were treated with different doses of the crude flavonoid, group III, IV and V were treated with 50, 100 and 200 mg/kg body weight of crude flavonoid respectively for14 days. Group II (ulcerated rats) which served as positive control received water. Group VI received omeprazole 20mg/kg body weight (standard anti-ulcer drug). Preliminary phytochemical screening of the extracted flavonoid confirmed the presence of flavonoid compound containing double bonds, with phenolic hydroxyl groups within its structure. There was a significant (p<0.05) increase in the activities of superoxide dismutase, catalase and reduced glutathione level in rats treated with different doses of crude flavonoid compared with ulcerated untreated rats (group II). The result shows that crude flavonoid from Schwenkia american improved the healing process of aspirin-induced ulcers in rats